Era of Artificial Intelligence prospects for Indian agriculture - Bhar, Lal Mohan; V, Ramasubramanian; Arora, Alka; Marwaha, Sudeep; Parsad, Rajender (Indian Farming, 2019)
Artificial intelligence (AI) is silently but increasingly entering Indian agriculture and enhence our society at large. Even though machine learning (which is a subset of AI) has been used for classifications and prediction purposes for, to cite a few, food grading, crop yield forecasting, and recently, a new set of deep learning algorithms have heralded the possibilities of taking the research and applications of AI to a much higher levels and with much more accuracy. Similarly, other AI techniques are making inroads in all fields including agriculture. Amid high expectations about how AI will help the common man and also transform his mind set, thoughts and attitude towards the benefits that it may bring, there are certain concerns about the illeffects of such sophisticated technologies as well. In the end, if AI systems can enhance farmers in terms of their social and economic wellbeing, we should be open to innovating new upcoming technologies with AI as their soul.